eSexualHealth: Preferences to use technology to promote sexual health among men who have sex with men and trans and gender diverse people - Esha Abraham; Esha Abraham; Eric P. F. Chow; Eric P. F. Chow; Eric P. F. Chow; Christopher K. Fairley; Christopher K. Fairley; David Lee; Fabian Y. S. Kong; Limin Mao; Jane L. Goller; Nicholas Medland; et al. (Frontiers Media S.A., 2023)
ObjectivesGay, bisexual and other men who have sex with men (GBMSM) and trans and gender diverse (TGD) people are disproportionately affected by poorer sexual health outcomes compared to heterosexual populations. We aimed to explore the preferences of GBMSM and TGD for using eHealth for sexual health (eSexualHealth).MethodsWe distributed an anonymous online survey from April to August 2021among the lesbian, gay, bisexual, transgender, intersex, queer and other people of diverse sexuality or gender (LGBTIQA+) community in Australia. The survey collected data on sociodemographic characteristics and sexual behaviors, their preferences for app/website functions and preferred HIV and sexually transmitted infection (STI) testing reminders. We used descriptive statistics to summarize the characteristics of the study population. Free-text responses were thematically analyzed.ResultsOf 466 participants included, most identified as cisgender males (92.7%). The median age was 48 [interquartile range (IQR): 37-56]. For accessing sexual health-related information, 160 (34.6%) would use either a website or an app, 165 (32.7%) would prefer a website, 119 (25.8%) would prefer an app, and 33 (7.1%) would not use either platform. There was no significant difference between GBMSM and TGD people. Participants were most interested in information about STI clinics, HIV/STI hotspots, and sexual health education. Participants stressed the need for privacy and anonymity when using eHealth. Regarding reminders to test for HIV/STIs, receiving regular SMS was most popular (112/293, 38.2%), followed by regular emails (55/293 18.8%) and a reminder function on their phone (48/293, 16.4%).ConclusionOur study suggests a promising future for eHealth among GBMSM and TGD people. Sexual health is still a stigmatized area, and eHealth may circumvent barriers this population faces.